Pengaruh Aktivitas Kerajinan Tangan terhadap Self Esteem pada Pasien Skizofrenia - Sekar Intania, Putri; Untari, Rita (Jurnal Terapi Wicara dan Bahasa, 2024)
Background: Schizophrenia is a severe thought process disorder with both positive and negative symptoms. Positive symptoms include delusions, hallucinations and thought disorder. Negative symptoms of schizophrenia include shallow affectivity, withdrawal from society and lack of willpower. The problem in schizophrenia patients that often arises is low self-esteem. This causes patients to interact less socially with their environment due to shyness and hallucinations. Schizophrenia patients avoid other people and crowds caused by low self esteem. Handicrafts are a solution to improve self-esteem, productivity, creativity, and motivation. Objectives: This study aims to determine the effect of handicrafts on self esteem in schizophrenia patients. Methods: This research is a quantitative research of pre-experimental model using one group pretest-posttest design. The sample population of this study were patients in the psychosocial rehabilitation unit of Dr. Arif Zainuddin Surakarta Hospital. Sampling using purposive sampling technique with a total of 22 samples. Hypothesis testing using paired sample t-test with the help of the SPSS version 25. Results: Based on the results of data analysis, the p-value hypothesis test was 0.000 (<0.05). These results indicate that handicrafts affect self esteem in schizophrenia patients. Conclusion: Handicraft activities affect self esteem in schizophrenia patients at RSJD Dr. Arif Zainudin Surakarta. Keywords: Handicrafts, Schizophrenia, Self esteem